The role of competitive intelligence and its sub-types on achieving market performance - Hamid Tahmasebifard (Cogent Business & Management, 2018)
During recent volatile and competitive environment, competitive intelligence (CI) has emerged and grown into a discipline to help organizations adapt to environmental change. Although existing literature provides a proper insight about the drivers of CI activities, its organization, usage and dissemination within firms, researches on the outcomes of CI activities as to whether these practices collectively have any relationship with performance are rare. Furthermore, there is no investigation on the influence of each subtype of CI on performance that could provide beneficial insight for managers to select their emphasis domains in CI activities and consequently achieving effectiveness and efficiency in marketing efforts. Especially, it could be more crucial in today's tough economic situation in which companies are gripped by widespread cost-cutting and layoffs programs. Thus, this paper analyzes the effect of CI and its subtypes on market performance. The results illustrate that CI positively affects market performance. Among subtypes of CI, competitor intelligence, market intelligence and technological intelligence leave the greatest impact, respectively.
Keywords: 650